DAMPAK GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN MELALUI AGENCY COST DAN KINERJA KEUANGAN - Abigail Maladi, Scarlet; Sofyaun, Ashari; Hernadi Moorcy, Nadi; Tangke Rante, Nely (Fakultas Ekonomi Universitas Balikpapan, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) on firm value through agency cost and financial performance in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Good Corporate Governance is proxied by managerial ownership, audit committee, and board of commissioners. Agency cost serves as the first intervening variable, while financial performance, proxied by Return on Assets (ROA) and Return on Equity (ROE), serves as the second intervening variable. Firm value is proxied by Price to Book Value (PBV). This research employs a quantitative approach using a purposive sampling technique. The sample consists of 20 manufacturing companies observed over a three-year period, resulting in 60 observations. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS version 4.The results indicate that Good Corporate Governance has a positive but insignificant effect on agency cost. Furthermore, Good Corporate Governance has a negative and insignificant effect on both financial performance and firm value. Agency cost has a positive but insignificant effect on firm value. Meanwhile, financial performance, as measured by ROA and ROE, has a positive and significant effect on firm value. The mediation analysis reveals that neither agency cost nor financial performance is capable of mediating the relationship between Good Corporate Governance and firm value in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period